Futures of science with and for society: towards transformative policy orientations. Issue 3 (13th June 2016) - van Oost, Ellen; Kuhlmann, Stefan; Ordóñez-Matamoros, Gonzalo; Stegmaier, Peter
Abstract : Purpose: How to derive policy implications from five future scenarios of transformed research and innovation (R&I) systems? This paper analyzes methodological and content issues of five future scenarios of transformed R&I systems. The aim of this paper is to provide an outlook on strategic policies capable of facilitating or moderating these transformative changes in R&I practices is discussed in light of overarching intentions to foster "responsible" ambitions (in Europe and beyond, discussed as responsible research and innovation, RRI). Design/methodology/approach: The paper elaborates a four-step methodology to assess the scenario's policy implications: first, by articulating the scenario implications for six core dimensions of R&I systems; second, an RRI assessment framework is developed to assess in each scenario opportunities and limitations for transforming R&I systems towards responsibility goals; the third involves a cross-scenario analysis of similarities and differences between the scenarios, allowing the identification of robust policy options that make sense in more than one scenario. The last analytical step includes again the richness of the individual scenario assessments aiming to provide a broader outlook on transformative policy orientations. Findings: The paper concludes with outlining the contours of a future-responsible R&I system together with some suggestions for transformative policy orientations that aim to govern the R&I system towards such a future, as a source of inspiration and reflection. Research limitations/implications: The analysis is based on five future scenarios that do not systematically cover future developments external to the R&I system. Practical Implications: An outlook of strategic policies capable of facilitating or moderating these transformative changes in R&I practices is discussed in light of the overarching European Union goal of encouraging the performance of RRI. Originality/value: This paper provides inspirational anticipatory strategic intelligence for fostering the responsible ambitions of research with and for society.